Discovering Risks for a Fertilizer Business in Madagascar when Collaborating with an Indonesian Company Case study: ABC company Start-Up in Madagascar - Sahondra, Vatsiniaina Tatamo; Chaerul D. Djakman (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study examines the strategic risks ABC Company may encounter in its collaboration with an Indonesian firm in the fertilizer industry. As a Madagascar-based startup specializing in mixed-blended fertilizers, ABC aims to enhance innovation and agricultural productivity through this partnership. However, challenges such as financial instability, supply chain disruptions, regulatory uncertainty, political influence, and corruption in customs clearance pose significant threats to business operations. Utilizing the COSO Enterprise Risk Management (ERM) framework (2017), this research systematically identifies and assesses these risks while proposing structured mitigation strategies. A qualitative methodology, incorporating semi-structured interviews and document analysis, offers deeper insights into risk prioritization. Findings reveal that despite ABC’s initial risk management efforts, several high-impact risks persist, requiring proactive intervention. The study underscores the importance of adopting COSO ERM principles, alongside strategies such as supplier diversification, compliance monitoring, blockchain-based customs tracking, and financial hedging, to safeguard operational stability. This research contributes new insights, as no prior studies have applied COSO ERM to similar international collaborations in the fertilizer sector.